KEHUJJAHAN HADÄªá¹ Iâ€™MAL LIDUNYÄ€ KAANNAKA TAâ€™ISá¸¤U ABADAN WAâ€™MAL LIAKHIROTIKA KAANNAKA TAMÅªTU GODAN SEBAGAI DALIL ETOS KERJA - Mahdalena Nasrun (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2022)
Iâ€™mal liddunyÄ kaannaka taâ€™Ä«syu abadan, waâ€™mal liÄkhirotika kaannaka tamÅ«tu godan very famous often quoted in various scientific articles. Whereas in fact, after reviewed furthermore this hadÄ«á¹¡ contradicts with the texts of the al-quran. The question in this research is whether this is a hadÄ«á¹¡? how is the hujjah hadÄ«á¹¡ i'mal liddunyaa kaannaka?. This research including a research library with approach a critical theory of matan hadÄ«á¹¡. The results of the research show that this is not a hadÄ«á¹¡, it is not found in the hadÄ«á¹¡ mu'tabar book; kutub al-tis'ah.Therefore this is just an expression (aá¹¡ar), in terms of sanad it is not marfu', not hadÄ«á¹¡ la ashla lahu. The source of this aá¹¡ar is thought to be from Ibn 'Umar, from Ali bin Abi Talib ra, from the words of 'Umar bin al-As. Matan criticism theory is used to evaluate aá¹¡ar, including its in not applicable (gair ma'mul bih). Contrary to a higher dalil, namely the al-quran. QS aÅ¼-Å»ÄriÄt verse 56 explains the essence of the purpose of human creation, namely to worship Allah SWT. In rhythm with QS al-Jumuah (62): 10) the order after praying is to seek sustenance. Likewise the same command to be balanced between the affairs of the hereafter and the world in QS al-Qaá¹£aá¹£ (28): 77. These verses are rules, guidelines, the spirit of motivation in carrying out every activity of human life in the world.